IDENTIFIKASI SEKTOR-SEKTOR EKONOMI UNGGULAN DI KABUPATEN TULANG BAWANG BARAT - Yudiansyah Yudiansyah; Dwi Haryono; Agus Hudoyo (Lampung University, 2019)
The ability of the region in spurring economic growth is highly dependent on the superiority or competitiveness of economic sectors in its region. The limited resources possessed by the West Tulang Bawang Regency, priority scale is needed for the development of leading sectors based on regional characteristics and their relevance to other regions. The main aim of this research is identify the leading economic sectors of West Tulang Bawang Barat Regency. This research uses some methods, are (1) Location quotient; (2) Shift-share; and (3) Input-Output. The results of the analysis show that the leading economic sectors in West Tulang Bawang Barat Regency are the food and beverage industry, information and communication, livestock, large and retail trade, and plantations. Keywords: input-output, leading sectors, location quotient, shift-share